Analysis of Factors Affecting the Achievement of the Immunization Program at Community Health Center Patek Darul Hikmah District Aceh Jaya - Diana Lestari; Ismail Efendy; Mayang Wulan (Newinera Publisher, 2022)
Complete immunization in healthy Indonesia demonstrates the importance and benefits of immunization for the health of children and the world community, addresses the immunization coverage gap through increased program investment, and conveys that complete routine immunization is the basis for strong health. The purpose of the study was to analyze the factors that influence the achievement of the immunization program at the Patek Health Center, Darul Hikmah District, Aceh Jaya Regency. This qualitative study contained a sample of 10 people, namely 3 main informants from the Head of the Patek Health Center, 1 immunization Programmer and 1 Implementing Midwife and 5 Village Midwives supporting informants and 2 Community. The results of the research explained by informants that Facilities and infrastructure Although there are still mothers who still do not want to bring their children to immunization, Process (planning, implementation, monitoring, evaluation) Planning for immunization activities every month, implementing posyandu not for immunization at Puskesmas, Monitoring monitoring of the local area (PWS), Evaluation of the level of immunization coverage for measles has not been achieved properly. The output of this activity is carried out with cross-programme, cross-sectoral collaboration, professional organizations, NGOs, and community officers/cadres. and Outcome of immunization achievement did not reach 85%. Conclusions and Suggestions It is hoped that as input for the Patek Health Center, Darul Hikmah District, that research provides a positive discourse to further improve the quality of Immunization Program Achievements so that it runs effectively.